Land Governance Assessment Framework : Rwanda - Ngoga, Thierry (World Bank, Washington, DC, 2017)
Rwanda has initiated a major land tenure reform program over the last two decades to clarify land rights, underpinned by far-reaching legal and institutional reforms (2004 national land policy (NLP); 2005 organic land law (OLL)), which culminated in a nationwide program of systematic land tenure regularization (LTR) that was completed in 2012. The implementation of the land governance assessment framework (LGAF) in Rwanda is timely and will help the country to take stock in a comprehensive way, benchmark, and assess priorities as input into ongoing policy, legal, and institutional reforms. LGAF was undertaken between September 2014 and May 2015, and validated in January 2016. The framework analysis is organized into nine modules: (i) land tenure recognition; (ii) rights to forest and common lands and rural land use regulations; (iii) urban land use, planning, and development; (iv) public land management; (v) process and economic benefit of transfer of public land to private use; (vi) public provision of land information; (vii) land valuation and taxation; (viii) dispute resolution; and (ix) review of institutional arrangements and policies.